Effects of fibre treatment on mechanical properties of kenaf fibre reinforced composites: a review - Hamidon, Muhammad Hafizal; Hameed Sultan, Mohamed Thariq; Ariffin, Ahmad Hamdan; Md Shah, Ain Umaira (Elsevier, 2019)
There have been review on kenaf fibre (KF) production and mechanical properties but lacks review on the treatment and surface modification on kenaf fibre. Therefore, this study is to show the type of treatment that have been done by previous researcher. A lot of methods have been investigated to find the optimum method to obtain better condition and properties for kenaf fibre. The present review describes those applied to kenaf fibre. The most widely used chemical treatment is the alkaline treatment using a sodium hydroxide (NaOH) solution, followed by a silane treatment. Variety of chemical concentration for NaOH solution and silane solution are investigated and a few combined treatments such as alkaline-silane, alkaline-steam, alkaline-radiation and alkaline-bleaching are also discussed. Thus, this paper presents an overview of investigated treatment methods with application to kenaf fibre and what are the effects of chemical treatment to the surface of kenaf fibre and the mechanical properties of the composites developed based on treated kenaf fibre.